Dampak Covid-19 pada Destinasi Pariwisata Prioritas Bromo Tengger Semeru - Wulung, Shandra Rama Panji; Latifah, Aifa Nurul; Saidah, Amalia Farhani; Ningtias, Audinna Sri; Yasyfa, Fatharani (Jurnal Ilmiah Pariwisata, 2021)
Bromo Tengger Semeru National Park as one of the national priority tourism destinations seeks to minimize the negative impact of Covid-19 as an effort to maintain tourism activities. The purpose of this study was to determine the impact of Covid-19 on the tourism destination of Bromo Tengger Semeru National Park. In addition, policies by destination managers and stakeholders are also reviewed in preventing the spread of the pandemic. The research approach uses qualitative with the type of data used is secondary data. Secondary data is obtained from previous research, policy documents, and the internet related to the unit of analysis which includes tourism destinations or tourist attractions, the tourism industry, tourism marketing, and tourism institutions. The results showed that Covid-19 had a negative or positive impact on tourism activities in the Bromo Tengger Semeru National Park. Managers and stakeholders establish policies with standard operating procedures for tourism activities in Bromo Tengger Semeru National Park. Destination marketing efforts are needed to attract tourists after the pandemic that focuses on improving hygiene, health, safety, and environmental sustainability. This is useful for building tourist confidence to return to the tourism destination of Bromo Tengger Semeru National Park. Keywords: Covid-19, Destination Management, Bromo Tengger Semeru National Park